Limitação do uso da voz na docência e a prática de atividade física no lazer: Educatel Brasil 2015-16 - Stephanie Mayra de Moraes (2018)
Introduction: Evidence indicates the teaching profession as a predictor for the higher incidence and prevalence of voice disorders. Quality of life can be affected by the restrictions and impediments at work generated by speech disturbances that encompass the changes in vocal functionality perceived by the individual during interpersonal communication. An increasing number of scientific evidence already indicates that physically underachieving teachers tend to have vocal disorders more often compared to those who engage in physical activity. In this sense, the influence of physical activity is notorious in health conditions and, because it helps to maintain and recompose the physical and psychological health of the worker, it is essential for good professional performance. Although the indication of the regular practice of physical activity is frequently in the phonoaudiological orientations to teachers, little is known, through scientific evidence, about their influence. Objective: To identify the prevalence of teaching problems due to the voice among teachers of Basic Education and to analyze their association with the practice of physical activity. Methods: Data from a telephone interview survey were used between the October 2015 and March 2016 representative samples (n = 6,510) of teachers from the Basic Education in Brazil (Educatel). To minimize the influence of individual factors on the target population , we chose to use the complex or stratified proportional sampling technique, with selection by simple random selection in the strata. The stratified sample was defined according to the distribution of the national education system of the School Census / INEP of the year 2014, by: age group: 34 years; between 35 and 44 years; between 45 and 54 years and 55 years; sex: male and female; large regions: South, Southeast, Midwest, Northeast and North; location / census area: rural and urban; administrative dependency of the school: state, municipal, private and others (include teachers working in federal schools, or simultaneously state and municipal, state and private, municipal and private schools and other combinations of administrative dependency); types of hiring: insolvency / permanent effective, temporary contract, private network, and contract CLT (Consolidation of Labor Laws) or others; educational stage: children, elementary, middle, EJA (Youth and Adult Education), professional and others (including teachers working in more than one stage of education). For this study we used the information of age and gender, analyzed as potential confounders of the main association investigated. After the separation of the sample by the extracts, the technique of simple random sampling for the selection of the participants in each extract was used. The variable response of this study comprises the teacher's report of problems in teaching because of the voice, measured by the question "In the last 4 WEEKS, are you having a problem at work or to develop your profession because of your voice? (Frequently | Sometimes | Rarely | Never or almost never). This issue was based on the Quality of Life Protocol (QVV). In the end, the question about teaching problems about the voice was turned into a dichotomous indicator, and their answers were recoded into: Yes (Frequently | Sometimes) and No (Rarely | Never or almost never). The explanatory variable refers to the indicator of sufficient physical activity in leisure, calculated in stages, considering the modality (to classify the intensity of physical activity as moderate or vigorous, based on the Compendium of Physical Activities of 2011), daily duration and frequency of this practice. From the calculation of minutes spent per week with the practice of physical activity in the leisure (obtained by multiplying the usual number of minutes of the practice episodes by the number of days of practice during a week, using the midpoint of the reported categories) the dichotomous indicator was calculated: <150 minutes per week of physical activity in leisure considered "insufficiently active" and 150 minutes per week of physical activity in leisure defined as "sufficiently active". The data analysis was studied using Poisson regression models, and the magnitude of the association was measured by prevalence ratios, with 95% confidence intervals and a statistical significance of 5%. Results: About one-fifth of teachers (20.5%) reported problems in teaching because of voice, while approximately one-third reported sufficient leisure time physical activity (150 minutes / week) (37.8%). Both sufficient physical activity practice and physical activity practice on five or more days per week were inversely associated with voice problems, both in bivariate models and in those adjusted for confounding variables (gender, age and working day). Conclusion: Teachers of Basic Education have a high prevalence of teaching problems because of their voice. Adequate practice of leisure physical activity and weekly practice for five or more days point to a reduction in the prevalence of teaching problems due to voice, regardless of gender, age group, and the teacher's weekly work schedule. This is the first national and representative study of teachers working in Basic Education in Brazil focused on the relationship between the use of voice in teaching and the practice of physical activity in leisure. Evidence is presented for the foundation of policies and programs to value the practice of physical activities and the promotion of health and disease prevention among teachers. It is necessary to promote the quality of life of the teacher, through the implementation of public policies that encourage the practice of physical activity, as well as the use of public spaces, city academies, bicycle paths, among other spaces designed for care with physical health. This initiative aims at valuing and recognizing the fundamental importance of teachers in the construction of society.